2016
DOI: 10.1002/anie.201609043
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Renal Clearance and Tumor Targeting of Ultrasmall Metal Nanoparticles with Particle Density

Abstract: Identifying key factors that govern in vivo behaviors of nanomaterials is critical to future clinical translation of nanomedicines. Shadowed by size-, shape- and surface-chemistry effects, the impact of particle core density on clearance and tumor targeting of inorganic nanoparticles (NPs) remains largely unknown. By utilizing a class of ultrasmall metal NPs with the same size and surface chemistry but different densities as model, we found that both renal clearance and passive tumor targeting of the NPs are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 45 publications
(38 reference statements)
1
77
0
Order By: Relevance
“…4 For example, we were able to synthesize GSH coated gold nanoparticles (GS-AuNPs), sliver nanoparticles (GS-AgNPs), and copper nanoparticles (GS-CuNPs) of 1.7 ~ 3 nm, which exhibited strong resistance to serum protein binding and effective renal clearance of >50% ID (injection dose) at 24 h post-injection (p.i.). 57 Similar renal clearance was observed from even smaller GS-AuNPs. 8 Efficient renal clearance of these zwitterionic metal NPs also found exciting applications in cancer diagnosis and kidney functional imaging.…”
supporting
confidence: 58%
“…4 For example, we were able to synthesize GSH coated gold nanoparticles (GS-AuNPs), sliver nanoparticles (GS-AgNPs), and copper nanoparticles (GS-CuNPs) of 1.7 ~ 3 nm, which exhibited strong resistance to serum protein binding and effective renal clearance of >50% ID (injection dose) at 24 h post-injection (p.i.). 57 Similar renal clearance was observed from even smaller GS-AuNPs. 8 Efficient renal clearance of these zwitterionic metal NPs also found exciting applications in cancer diagnosis and kidney functional imaging.…”
supporting
confidence: 58%
“…[8] After intravenous injection, they are not only eliminated through the urinary system [8a,b] and report on the kidney function [9] but can also target a variety of tumor models through the EPR effect. [10] Over the past few years, many other renal-clearable nanostructures have also been developed. [11] More importantly, a recent clinical trial with “C” dots has clearly demonstrated the great promise of these renal-clearable NPs in cancer diagnosis in the clinic.…”
mentioning
confidence: 99%
“…Considering that the GS-AuNPs and GC-AuNPs are both much smaller than the pore size of tumor leaky vasculature, [21] a possible reason for the differences in the distribution half-lives is that the GS-AuNPs (zeta potential: −48.0 ± 2.3 mV, pH 7.4) are much more negatively charged than the GC-AuNPs (zeta potential: −22.1 ± 3.6 mV, pH 7.4) and might marginate to the blood vessel wall more slowly than the GC-AuNPs. [10c] Such charge-dependent pharmacokinetics have been observed for molecular agents, [19] small, few-nanometer-sized antibodies, [22] as well as engineered NPs. [23] …”
mentioning
confidence: 99%
“…Therefore, prolonged blood circulation could be achieved with the 3-nm AuNPs as compared with the 18-nm AuNPs. Additionally, we recently reported that ultrasmall metal NPs with higher density (AuNPs) can marginate more rapidly to the blood vessel walls; as a result, in the laminar blood flow, the AuNPs have long blood retention, which allows them to accumulate in tumors more efficiently [42]. …”
Section: Resultsmentioning
confidence: 99%